PENGARUH INVESTASI TERHADAPAN PENYERAPAN TENAGA KERJA PADA INDUSTRI KERAJINAN DI SURABAYA (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
Investment is a driving factor to drive the economy or economic activity in an area. If the level of investment increases then more and more economic activity of Surabaya City. Employment opportunities may also increase due to the number of economic activities that take place and the welfare of the community will certainly be better. This study examines the effect of investment on employment in the handicraft industry in Surabaya. The purpose of this study is to find out whether the investment affect the absorption of labor in the handicraft industry in the city of Surabaya so that later it is expected to be used as one of the basic in policy termination in overcoming labor problems in Surabaya. The data used in this study is sekuder data obtained from the Department of Trade and Industry (DISPERINDAG) Surabaya. While the method of analysis used in this study is a simple regression analysis method with the help of SPSS. The results of this study indicate that there is a very strong and positive relationship between investment with employment absorption. The results of t test show the significance is smaller than 0.05, so it can be deduced "If there is a change in the value of investment it will affect the absorption of the number of workers in the handicraft industry sector. Result of correlation coefficient obtained equal to 0,963 from variable of labor absorption and correlation of whole variable is equal to 0,963.Â Keywords: Investment, labor absorption, handicraft industry.